Peluang Efisiensi Penggunaan Energi pada Sektor Perhotelan di Kota Jambi - Myson Myson (Jurnal Civronlit Unbari, 2018)
In the RPJMN 2015-2019 the government sets a target of 20 million foreign tourists by 2019. The hotel sector contributes to national energy use of 3%. The hospitality sector is growing at a 12.5% growth rate from 2007 to 2011, in response to an increase in the number of tourists between 9-13% including in Jambi at that time. To evaluate the use of electric energy at the hotel it is necessary to conduct an analysis of energy costs per hotel room sold to give an average picture of energy costs. From the calculation, it is found that the intensity of energy consumption in one of the hotel rooms in jambi city is 5.93 kWh / m2.Key words: Energy, energy conservation, hotel